2021
DOI: 10.1111/head.14122
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 randomized placebo‐controlled study of lasmiditan for the acute treatment of migraine in Japanese patients

Abstract: Objective: To evaluate the efficacy and safety of lasmiditan in Japanese adults with migraine.Background: Global clinical studies have demonstrated the efficacy and safety of lasmiditan in the acute treatment of migraine.Methods: This was a multicenter, randomized, double-blind, placebo-controlled, phase 2 study in Japan (NCT03962738), which enrolled adults with migraine with or without aura. Participants were randomized 7:3:7:6 to placebo, lasmiditan 50 mg, 100 mg, or 200 mg to be self-administered orally wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(94 citation statements)
references
References 19 publications
6
74
1
Order By: Relevance
“…29,34 The only Asian-based clinical trial on MBS was conducted in Japan and revealed photophobia to be the most common MBS but at a lower frequency (37.4%). 43 In an observational study by the Japanese Adelphi Migraine Disease-Specific Programme, the most frequent physician-reported symptoms that were considered most troublesome to patients (defined as occurring in ≥5% of patients with episodic migraine [EM] or CM) were pain-related symptoms. These symptoms included unilateral pain (50.8% and 37.7% for EM and CM, respectively), pulsating/throbbing pain (20.8% and 37.7% for EM and CM, respectively), nausea (7.5% for CM), and vomiting (7.5% for CM).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…29,34 The only Asian-based clinical trial on MBS was conducted in Japan and revealed photophobia to be the most common MBS but at a lower frequency (37.4%). 43 In an observational study by the Japanese Adelphi Migraine Disease-Specific Programme, the most frequent physician-reported symptoms that were considered most troublesome to patients (defined as occurring in ≥5% of patients with episodic migraine [EM] or CM) were pain-related symptoms. These symptoms included unilateral pain (50.8% and 37.7% for EM and CM, respectively), pulsating/throbbing pain (20.8% and 37.7% for EM and CM, respectively), nausea (7.5% for CM), and vomiting (7.5% for CM).…”
Section: Discussionmentioning
confidence: 99%
“…27,28 To date, most of the recent clinical trials adopting MBS as a co-primary endpoint have been conducted in Europe and the United States, [29][30][31][32][33][34][35][36][37][38][39][40][41][42] except for one study in Japan. 43 These studies reported photophobia as the most common MBS, ranging from 50.6% to 59.9% in patients from Europe and the United States; however, the frequency was noticeably lower in Japan (37.4%). [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Because regional variations likely exist in migraine prevalence and manifestations, it is of interest to explore MBS prevalence and distribution in Taiwanese patients with migraine, and we hypothesized that the MBS prevalence and distribution might differ between migraine subtypes.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations